Pengaruh Kepemimpinan Yang Melayani Dan Pengembangan karir Terhadap Kinerja Pegawai Dengan Dimediasi Organizational Citizenship Behavior (OCB) - Donny Agus Kurnianto; Bambang Suko Priyono (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2023)
The purpose of this research is to analyze the influence of servant leadership and career development on Organizational Citizenship Behavior (OCB). Analyzing the influence of servant leadership and Organizational Citizenship Behavior (OCB) on employee performance. Analyzing Organizational Citizenship Behavior (OCB) mediates the influence of servant leadership and career development on employee performance. The population in this study were employees of the Center for Textile and Footwear Products Industry (BIPTAK) of the Department of Industry and Trade of Central Java Province, amounting to 105 people. The sample in this study were employees of the Center for Textile and Footwear Products Industry (BIPTAK) of the Department of Industry and Trade of Central Java Province. Sampling by census sampling technique of 105 employees. Methods of data collection using a questionnaire. Data analysis used linear regression analysis. Based on the results of the study, it can be concluded that servant leadership and career development have a positive and significant effect on Organizational Citizenship Behavior (OCB). Servant leadership, career development and Organizational Citizenship Behavior (OCB) have a positive and significant effect on employee performance. Organizational Citizenship Behavior (OCB) mediates the influence between leadership and does not mediate the influence between career development on employee performance.